Across, and in-between, image, text and Typography in Graphic Design - Zantides, Evripides (My University, 2023)
The process of visualizing verbal and cognitive information in graphic communication is a complex and dynamic interplay between language and design, using images and typographic characters. Written text is inherently multimodal, with semiotic characteristics that contribute to its linguistic meaning from different perspectives, while images can be iconic or symbolic with more complex semiotic interpretations. Moreover, letterforms represent phonetic sounds and, when combined with images, create additional interrelationships that impact message communication. This paper utilizes semiotic analysis, drawing on Bertin's (1967) theory on the semiology of graphics, to investigate the relationships between image and text in a series of advertisements that use visual metaphor as a major technique in their construction of messages. Specifically, the study examines the visualization of verbal messages in terms of their shape, size, color, tone, texture, placement, and orientation, as well as in relation to metaphoric imagery. The findings suggest that the process of interpretation not only requires a correlation between verbal and nonverbal elements but also necessitates knowledge across and in-between the metaphoric signs used within the images.
Keywords: Semiotic analysis